Economic Growth And Carbon Emissions: An ARDL Panel Study Of 10 Asean Countries - Dian Priastiwi; Anisa Fatmawati (Jurnal Ilmu Ekonomi JIE, 2026)
An increase in carbon dioxide emissions accompanies the rise in economic activity. This study analyzes the short-run and long-run relationship between economic growth and CO₂ emissions, focusing on 10 ASEAN countries from 1990 to 2022. A quantitative approach is employed using the Panel Autoregressive Distributed Lag (Panel ARDL) model with the Pooled Mean Group (PMG) estimation method. The results indicate that economic growth and population have a positive and significant impact on CO₂ emissions in the long run. In the short run, the Error Correction Term (ECT) indicates an adjustment mechanism toward long-run equilibrium, with individual-country analysis revealing heterogeneity in adjustment speed. Only Cambodia and Laos demonstrate a strong and significant ECT adjustment mechanism, while other countries show slow or ineffective adjustments. This study contributes to the literature by analyzing the interaction between economic growth and environmental sustainability in the ASEAN context.